Taxing Away M&A: The Effect of Corporate Capital Gains Taxes on Acquisition Activity - Lars P. Feld; Martin Ruf; Ulrich Schreiber; Maximilian Todtenhaupt; Johannes Voget (Center for Economic Studies and ifo Institute (CESifo), 2016)
Taxing capital gains is an important obstacle to the efficient allocation of resources because it imposes a transaction cost on the vendor which locks in appreciated assets by raising the vendor's reservation price in prospective transactions. For M&As, this effect has been intensively studied with regard to shareholder taxation, whereas empirical evidence on the effect of capital gains taxes paid by corporations is scarce. This paper analyzes how corporate level taxation of capital gains affects inter-corporate M&As. Studying several substantial tax reforms in a panel of 30 countries for the period of 2002-2013, we identify a significant lock-in effect. Results from estimating a Poisson pseudo-maximumlikelihood (PPML) model suggest that a one percentage point decrease in the corporate capital gains tax rate would raise both the number and the total deal value of acquisitions by about 1.1% per year. We use this result to estimate an efficiency loss resulting from corporate capital gains taxation of 3.06 bn USD per year in the United States.
Keywords: H25; G34; 330; corporate taxation; M&A; capital gains tax; lock-in effect